Millennium Development Goals for Health in Europe and Central Asia : Relevance and Policy Implications - World Bank (Washington, DC, 2013)
This study aims to contribute to the debate about the appropriateness of health-related Millennium Development Goals (MDGs) for the countries of the Europe and Central Asia region. It is primarily addressed at policy advisors and senior analysts at the local, regional, and global level, who could influence the strategic directions of policymakers. The study is of particular relevance to international development institutions and UN organizations, who might have to reconsider the focus of their health-related development assistance to the countries of the ECA region. The study examines how appropriate the health-related MDGs are for the countries of the ECA region by analyzing the impact of the following four scenarios on life expectancy at birth: achieving MDG targets for infant, child, and maternal mortality; reducing infant, child, and maternal mortality to EU levels; reducing infant, child, and maternal mortality to the lowest subregional levels; reducing deaths from cardiovascular disease and external causes of death to EU levels. Because national registration data on infant and child mortality in countries of Central Asia and the Caucasus underestimate the true figure, the first three scenarios were recalculated for these countries in an additional calculation, using survey-based World Bank data.